2000
DOI: 10.1046/j.1570-7458.2000.00685.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in female sex pheromones of the rice leaffolder moth, Cnaphalocrocis medinalis: identification of pheromone components in Japan

Abstract: Sex pheromone components of the Japanese rice leaffolder moth, Cnaphalocrocis medinalis Guenée (Lepidoptera: Pyralidae) were identified from ovipositor extracts of virgin females as (Z)‐11‐octadecenal, (Z)‐13‐octadecenal, (Z)‐11‐octadecen‐1‐ol and (Z)‐13‐octadecen‐1‐ol at a ratio of 11:100:24:36 by GC‐EAD, GC, GC‐MS. The total amount was estimated to be ca.0.9 ng/female. Field bioassays in Kagoshima, Japan, showed that the two aldehydes are essential for male attraction and the alcohols may have a synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 8 publications
2
28
3
Order By: Relevance
“…In the report regarding the identification of the Philippine blend, no behavioral activity has been demonstrated; only EAG activity was reported (Ramachandran et al, 1990). In our analyses, neither Z11-16:Ac nor Z13-18:Ac were detected in the crude extract of Japanese populations (Kawazu et al, 2000).…”
Section: Introductioncontrasting
confidence: 86%
See 4 more Smart Citations
“…In the report regarding the identification of the Philippine blend, no behavioral activity has been demonstrated; only EAG activity was reported (Ramachandran et al, 1990). In our analyses, neither Z11-16:Ac nor Z13-18:Ac were detected in the crude extract of Japanese populations (Kawazu et al, 2000).…”
Section: Introductioncontrasting
confidence: 86%
“…Synthetic monounsaturated aldehydes, alcohols and acetates were synthesized by Shin-Etsu Chemical Company (Tokyo, Japan). The compounds were purified by column chromatography in the same manner as reported in our previous report (Kawazu et al, 2000). Gas chromatographic (GC) analyses showed that the purified compounds contained Ͻ0.1% of the corresponding E-isomers (Kawazu et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations